Morphological Alignment in Khorramabad Lori Language - Fatemeh Akoondi (̒Ilm-i Zabān, 2023)
Every region’s language and dialect have a main influence on the formation of the people’s worldview and identity, but recently these languages and dialects have been left and ignorance endangered for reasons such as the effect of the standard language and inattention of the native speakers. Therefore, the purpose of this essay presentation is to register and reserve one of these endangered local varieties. In the present study, agreement and case categories as two main elements of morphological alignment typology in the Khorramabad Lori language were surveyed. The method included preparing a 340 sentences questionnaire, interviewing 3 native speakers, registering, recording, transcribing, describing, and analyzing dialectal data, and at the end, eliciting grammatical patterns of the case and agreement categories in this language. Findings revealed that it is a nominative-accusative pattern for agreement and case categories in Lori. Finally, it was deduced that the typological system of morphological alignment is nominative-accusative consistently in the Khorramabad Lori language.